Rural schools that are not in the countryside in the Regional Education Center of Foz do Iguaçu-PR - Marcus Pereira Andrade; Valdemar João Wesz Junior (Universidade Federal do Norte do Tocantins, 2024)
This study researched rural schools in the municipalities that make up the Regional Education Nucleus (NRE) of Foz do Iguaçu (Paraná), problematizing the fact that some educational institutions are called "from the countryside", but in fact are not located in the field. This study adopted a qualitative approach of an exploratory nature, using documental and bibliographical analysis, in addition to the systematization of secondary data. There was a situation of rural schools that are outside the countryside, using school transport as a service strategy. The prevalence of rural schools in the municipal network is verified in rural areas in relation to the state network, which indicates the gap in the offer of Secondary Education in this space. In conclusion, it is clear that rural schools are still spaces in dispute, both in the fight against closure processes and in the construction of elements and concepts of Rural Education that have not yet been assumed or recognized.